2019
DOI: 10.1088/1361-6552/ab2568
|View full text |Cite
|
Sign up to set email alerts
|

Low cost automatic IV curve generator for solar cells

Abstract: A simple and economical system that allows one to obtain the characteristic I-V curve in solar cells is presented. It is a computer-controlled system suitable as an instrumentation project for students who are learning about photovoltaic systems. This system is based on the use of an R-3R ladder circuit as a variable resistive load for a solar cell and is controlled by a microcontroller system connected to a PC. The system allows us to generate the I-V curve and calculates the parameters I sc , V oc , P max .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…These do not allow modifications to expand their operating characteristics, so there is a tendency to build them based on a heterogeneous set of hardware and software technologies [16]. Non-commercial tracers are based on hardware devices such as microcontroller (MCU) ATMega2560 [17], [18], ATMEGA328 [19], Atmel SAM3X8E [20], MSP430 [21], TivaC [22], PIC18F46K22 [23], and Raspberry PI [16], which are used for validation of laboratory prototypes, automation of measurement and visualization processes [18] using, in most cases, devices with low hardware resources [24]. In addition, some solutions perform the presentation of the results, trace curves, using standard computer equipment, databases [16], [18], [19], data analysis software such as MATLAB [21], Labview [22] and Python [19], [16], without considering local monitoring capabilities such as liquid-crystal display (LCD) touch screens [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These do not allow modifications to expand their operating characteristics, so there is a tendency to build them based on a heterogeneous set of hardware and software technologies [16]. Non-commercial tracers are based on hardware devices such as microcontroller (MCU) ATMega2560 [17], [18], ATMEGA328 [19], Atmel SAM3X8E [20], MSP430 [21], TivaC [22], PIC18F46K22 [23], and Raspberry PI [16], which are used for validation of laboratory prototypes, automation of measurement and visualization processes [18] using, in most cases, devices with low hardware resources [24]. In addition, some solutions perform the presentation of the results, trace curves, using standard computer equipment, databases [16], [18], [19], data analysis software such as MATLAB [21], Labview [22] and Python [19], [16], without considering local monitoring capabilities such as liquid-crystal display (LCD) touch screens [23].…”
Section: Introductionmentioning
confidence: 99%
“…Non-commercial tracers are based on hardware devices such as microcontroller (MCU) ATMega2560 [17], [18], ATMEGA328 [19], Atmel SAM3X8E [20], MSP430 [21], TivaC [22], PIC18F46K22 [23], and Raspberry PI [16], which are used for validation of laboratory prototypes, automation of measurement and visualization processes [18] using, in most cases, devices with low hardware resources [24]. In addition, some solutions perform the presentation of the results, trace curves, using standard computer equipment, databases [16], [18], [19], data analysis software such as MATLAB [21], Labview [22] and Python [19], [16], without considering local monitoring capabilities such as liquid-crystal display (LCD) touch screens [23]. In addition to this, validations of the systems are carried out only with simulation [25] or using synthetics [19], [20], therefore the mentioned limitations can be reduced by adding wireless transmission capabilities [26], granting mobility to the device and contributing to reduce the gap in your research with solutions based on portable and ubiquitous systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquity of solar cells has made them objects of interest in science and engineering education [4][5][6][7]. Nowadays, many high school or undergraduate physics classrooms and laboratories have produced experimental or practical works on solar cells [3,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we found that when students use ammeters and voltmeters to measure data during the experiment, the output of PV modules is affected by the changes of ambient light and temperature, resulting in the unstable reading of the ammeter. Therefore, real-time automatic I-V data acquisition and curve generation in solar cells experiment teaching are essential and some papers reported the real-time data acquisition and automatic I-V curve generation schemes based on Arduino systems [3,10].…”
Section: Introductionmentioning
confidence: 99%